KERAGAMAN JENIS DAN POTENSI PATI SAGU (Metroxylon sp) DI PULAU BUANO KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Komul, Yulianus Dominggus; Aponno, Hendrik Steven Eka; Wairisal, Pieter (Jurnal Hutan Tropis, 2025)
Buano is one of the small islands located in the western part of Seram Island with an area of approximately 135.73 km2, and it has the potential of natural resources such as forest products other than wood, which can contribute to the economic income of its community, one of which is Sago (Metroxylon sp). This research aims to determine information related to the diversity of species and the potential of Sago and its availability in meeting the needs of the community of Buano Island in West Seram Regency. The method used to calculate species diversity uses the analysis of Importance Value Index (Soerianegara and Indrawan, 1976) and Shannon Winner's Diversity Index (1954). Meanwhile, for the calculation of sago starch potential, it is estimated using the correlation equation developed by Yumte (2008). The correlation variables used are the average diameter at breast height (Dbh) and the average height of the canopy (Tbp). Measurement of data on diameter at breast height and canopy height is carried out on each tree with the logging ripe classes M1 and M2. The research results show that there are 2 types of sago found on Buano Island, namely Tuni/Laluli (Metroxylon rumphi Mart) and Molat/Manate (Metroxylon sago var molat). The Tuni/Laluli type (Metroxylon rumphi Mart) is the type of sago with the highest dominance level with INP values at each stage of growth. The potential of sago starch in the form of wet weight from the 2 types found is 25.86 tons/ha for the logging ripe phase and 72.53 tons/ha for the phase that is not yet logging ripe.